ENHANCING YOUNG LEARNERS’ SPEAKING PROFICIENCY THROUGH ENGAGING CLASSROOM ACTIVITIES (Journal of Uzbekistan’s Development and Research, 2025)
This article discovers that in early childhood education, the ability to speak confidently and effectively in a second language plays a foundational role in a learner’s overall language development. This article investigates how diverse classroom activities can foster young learners’ speaking skills. Emphasis is placed on the interaction between cognitive development, motivation, and activity design. It also explores how modern technologies and multilingual classroom dynamics influence oral language acquisition. Practical recommendations are presented for language teachers working with primary-level learners in both monolingual and multilingual settings.